Role of tick infestation in the progression of Anaplasma phagocytophilum infection in lambs - M. Groenevelt; S.R. Wijburg; H. Sprong; K. Kerkhof; S. Stuen (Ticks and Tick-Borne Diseases)
Tick Borne Fever (TBF) is a serious health condition in sheep, caused by infection with Anaplasma phagocytophilum. When secondary bacterial infections occur in TBF, it can progress to tick pyemia, a condition causing severe morbidity and mortality in flocks. The mechanisms that underly the severe effects of tick pyemia are not fully understood. Here, we hypothesized that tick bites during an established A. phagocytophilum bacteremia could aggravate immunosuppression, increasing the risk of secondary infections. In this study, four groups of four lambs were compared based on their clinical and hematological outcomes. Group A received an intravenous injection of A. phagocytophilum on day 0. Group AT received the same injection on day 0, followed by tick placement on their backs on day 4. Group T was exposed only to tick placement on day 4, while Group C received no treatment. The animals were clinically and hematologically assessed over 28 days, and ticks collected off their backs after feeding were analyzed. Both clinically and hematologically, no additional detrimental effects were seen in Group AT compared to Group A. All lambs in Group T also developed TBF, but their clinical and hematological outcomes were less severe than those in Groups A and AT. Serologically, all animals responded similarly, corresponding to the day of exposure to A. phagocytophilum. PCR results showed no significant differences among groups, although duration of follow-up may have influenced the results, as only Group AT lambs remained PCR positive on the final testing day. When ticks that fed on Group AT lambs were compared to either ticks fed on Group T lambs or unengorged ticks harvested from the same fields, it became clear that sheep act as amplifier hosts for A. phagocytophilum in ticks shortly after exposure to infected ticks. Among the unengorged ticks, 10.2 % were infected with A. phagocytophilum, compared to 67 % and 99.2 % of the engorged ticks from Groups T and AT, respectively. In contrast to A. phagocytophilum, sheep were refractory hosts for Borrelia burgdorferi s.l., as the percentage of infected ticks was 10.2 % in the unengorged ticks and only 1 and 1.7 % in engorged ticks from groups T and AT, respectively. In this study, additional tick bites did not contribute to immunosuppression in lambs during an established A. phagocytophilum bacteremia.